An unusual chiral-at-metal mechanism for BINOL-metal asymmetric catalysis - Zhenxing Li; Pengfei Chen; Zhigang Ni; Liuzhou Gao; Yue Zhao; Ranran Wang; Congqing Zhu; Guoqiang Wang; Shuhua Li (Nature Communications)
Abstract Chiral binaphthols (BINOL)-metal combinations serve as powerful catalysts in asymmetric synthesis. Their chiral induction mode, however, typically relies on multifarious non-covalent interactions between the substrate and the BINOL ligand. In this work, we demonstrate that the chiral-at-metal stereoinduction mode could serve as an alternative mechanism for BINOL-metal catalysis, based on mechanistic studies of BINOL-aluminum-catalyzed asymmetric hydroboration of heteroaryl ketones. Theoretical calculations reveal that an octahedral stereogenic-at-metal aluminum alkoxide species is the most stable species within the reaction system, and also is the catalytic relevant intermediate, promoting the stereo-determining hydroboration reaction through a ligand-assisted hydride transfer mechanism rather than the conventional hydroalumination mechanism. These computations reproduce the experimental selectivities and also rationalize the stereoinduction mechanism, which arises from the aluminum-centered chirality induced by chiral BINOL ligands during diastereoselective assembly. The reliability of the proposed mechanism could be verified by the single-crystal X-ray diffraction characterization of the octahedral aluminum alkoxide complex. Additional NMR and Electronic Circular Dichroism (ECD) experiments elucidated the behavior of the hexacoordinated aluminum alkoxide in the solution phase. We anticipate that these findings will extend the applicability of BINOL-metal catalysis to a broader range of reactions.